Inter-teaching: Improving the Academic Performance of Auditing Students in Vietnam - Mark Wheaton; Brendan O'Connell; Premasiri Yapa (Australasian Accounting, Business and Finance Journal, 2017)
The aim of this study is to investigate the effectiveness of inter-teaching; a student engagement pedagogy associated with behavioural and engagement theories and designed to engage students in their own learning. This methodology was introduced as a response to create a more positive outcome for students studying an auditing course who have historically experienced difficulties with successfully completing the subject. Inter-teaching was implemented and its effectiveness measured by comparing the final exam grade distributions from inter-teaching and the lecture tutorial teaching methods. Using a quantitative research methodology, students fail grade distributions were significantly lower in the inter-teaching semesters compared to previous semesters where the instructional method of teaching was the lecture model. The results suggested that inter-teaching may be a more effective method of teaching, resulting in an improved academic performance in the auditing course. It is expected that this study will contribute towards the effectiveness of student learning, an improvement in pass rates, and overall greater student satisfaction in advanced accounting courses.
Keywords: Inter-teaching; Lecture Tutorial; Student Engagement; Independent Learning; Group Discussions; Interteaching